2016
DOI: 10.2106/jbjs.15.00181
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiographic Outcomes of the Simpliciti Canal-Sparing Shoulder Arthroplasty System

Abstract: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(69 citation statements)
references
References 33 publications
4
65
0
Order By: Relevance
“…In contrast, some studies with short and mid-term follow-up have noted revision rates from 9% to 11.1% 209,215 . A recent multicenter study revealed only 3 complications and no revisions in 149 patients after 2 years of clinical and radiographic follow-up 216 .…”
Section: Stemless Modular Shoulder Arthroplastymentioning
confidence: 99%
“…In contrast, some studies with short and mid-term follow-up have noted revision rates from 9% to 11.1% 209,215 . A recent multicenter study revealed only 3 complications and no revisions in 149 patients after 2 years of clinical and radiographic follow-up 216 .…”
Section: Stemless Modular Shoulder Arthroplastymentioning
confidence: 99%
“…However, there is not yet any test available to objectively determine bone quality pre- or intraoperatively [29]. Churchill et al [18] described the use of a “thumb test” in which bone quality is intraoperatively assessed by compressing the surface of the neck cut with the thumb. Overall, the presently reviewed studies reported only a few isolated cases of loosening of the stemless component.…”
Section: Discussionmentioning
confidence: 99%
“…It comprises two pieces—a humeral implant and a head implant—which are available in different sizes. Churchill et al [27] and Ho et al [18, 28] both recently published results of canal-sparing respectively stemless shoulder arthroplasty with a 24-month follow-up in a total of 298 patients. Table 2 summarizes the indications.…”
Section: Simpliciti Stemless Prosthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Via this model, a central wire was placed in the humerus and the metaphysis was prepared using a drill and an impaction instrument (Figs. 5,b,and 6,b). Then, the anchor was positioned in the metaphysis, and the humeral head was placed on top of the anchor (Fig.…”
Section: Surgical Techniquementioning
confidence: 99%